Genome Wide Association Study Identifies Candidate Loci or Genes Responsible for Bacterial Stalk Rot Resistance in Maize - Mienanti, Devi; Hidayat, Iqbal; Danaatmadja, Yanuar; Belaffif, Mohammad Bahrelfi; Waluyo, Budi; Sugiharto, Arifin Noor; Kumar, Ajay Goel; Kuswanto, Kuswanto (AGRIVITA Journal of Agricultural Science, 2024)
Bacterial stalk rot (BSR) disease is caused by Dickeya zeae, where infection on maize could lead to an enormous yield loss. Although curative action to control BSR infection can be done using bactericides, preventing the establishment of infection is still the best approach in minimizing potential yield loss. Among the different methods in preventing BSR infection, the use of resistant maize hybrid is considered the best approach. In this study, Genome Wide Associated Study (GWAS) was employed to find SNP markers associated with BSR resistance in maize. Six hundred twenty four lines were divided into two observation groups and further phenotyped for BSR resistance at 5, 10, and 15 days after inoculation (DAI) with BSR. GWAS was performed in a time-series manner using MLM (Mixed Linear Model) controlling for population structure and kinship. We found one SNP marker in chromosome 2 displaying significant association to BSR resistance spanning the entire observation periods. We also found SNP markers with significant association to BSR spanning two consecutive observation days located in chromosome 2 and 5. These results would hopefully contribute to the development of hybrid maize with better resistance against BSR.